AN EVALUATION OF TEACHING STAFF MOBILITY IN ERASMUS PROGRAMME AND SUGGESTIONS FOR THE PROBLEMS : IN THE CASES OF ONDOKUZ MAYIS UNIVERSITY AND ERZINCAN UNIVERSITY - Adnan OFLAZ (Fırat University, 2019)
The Erasmus Program is a European Union program so as to encourage higher education institutions to cooperate with each other. In this program, it is aimed that all member countries of the European Union as well as candidate countries for membership produce joint projects with each other and have short-term student and academic staff exchanges. Since 2004, our staff and students have participated in this exchange program. They undoubtedly encountered some problems during this period. In this research, the aim is to describe frequently encountered problems by the academic staff and to propose recommendations for the solution about the Erasmus Teaching Staff Mobility Programme. This study is a qualitative research. The data for this research were obtained from twenty academic staff in two state universities (Ondokuz Mayıs University and Erzincan University) in academic year 2015-2016. Semi-structured interview is used as the data collection tool. At the end of the study, it can be said that participants have joined the programme for “recognizing educational systems of a different country”, “vocational development”, “gaining abroad experience”. The expectations of the instructors were met in “recognizing a different university” and “high scientific research level of the host university”. They had the opportunity to “recognize instructors and students in the host university” and “improve their foreign language skills and consequently increasing self-confidence”. They encountered some problems “such as short programme duration”. They offered also some suggestions such as expanding the duration of the programme, increasing the amount of the grant and increasing in the number of the bilateral agreements with universities”. The academic staff who experienced this programme should share their experiences with future Erasmus beneficiaries. The publication of a guidebook is suggested for future Erasmus beneficiaries with practical information regarding studying in partner university. In order to to encourage (departmental) Erasmus Coordinators, who increase the number of bilateral agreements, payments should be made.